SIMILE IN THE NOVEL THE KITE RUNNER BY KHALED HOSSENI - Marzyana Putra, I Putu Troy (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The study entitled “Simile in the Novel The Kite Runner by Khaled Hosseini” is focused on: (1) the kinds of simile terms of function, and (2) the meaning of simile found in The Kite Runner. The data were taken from a novel entitled The Kite Runner by Khaled Hosseini. The data were collected by reading the novel intensively and taking note of the similes found in the novel page by page. The collected data were analyzed using qualitative method based on the theory of figurative language, particularly simile. In the analysis, the kinds of simile in terms of function, and the meaning of each simile were presented. The main theory used in the analysis of the kinds of simile is the theses proposed by ”Zhang Xiu Guo” in a book under the title English Rhetoric, while the analysis of the meaning is based on the theory proposed by Leech in a book under the title Semantics. Based on the result of the analysis three kinds of simile in terms of function, namely descriptive, illuminative, and illustrative. The descriptive similes were found the most. The meanings of similes tend to be positive or negative based on the context in which similes were used. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: figurative language, simile, kinds of simile, meaning.